Pulmonary ultrastructure of the late aspects of human paraquat poisoning. - Dearden, L. C. (1978)
The pulmonary ultrastructure of the late aspects of a case of human paraquat poisoning is investigated and compared with normal human pulmonary ultrastructure. Alveoli in the paraquat patient are numerically reduced in comparison to the control. They are filled with edematous proteinaceous plasma-like fluid containing erythrocytes, macrophages, leukocytes, fibroblast-like cells, platelets, and fibrin. These alveoli are lined by granular pneumocytes. Interstitial areas in the paraquat patient are greatly expanded and there are no alveolar septums. Interstitial areas contain proteinaceous plasma-like material, collagen, fibrin, platelets, mature fibroblasts, plasma cells, many leukocytes, numerous erythrocytes, and capillaries. Capillary permeability seems to be enhanced in the paraquat patient either by vesicles forming transendothelial channels or pores or by disruption of endothelial cells.